Design and simulation of hybrid piezo-pyroelectric energy conversion device / Nurul Adina Azman - Nurul Adina, Azman (2021)
Sustainable energy had been eye as a huge opportunity to replace current fossil energy since it can be harvest in various forms. This study focusing on piezoelectric energy and pyroelectric energy which involves heating and vibration energy sources considering it is common phenomenon produce by numerous mechanical systems for example car engine and HVAC system. This study aims to design and simulate the performance of hybrid piezo-pyroelectric energy for low grade applications. The design of the hybrid piezo- pyroelectric conversion device is done by using SolidWorks. This study introduces performance of the device when different air heat temperature and force by air flow release from condenser is applied to the device. ANSYS is used for analytical calculation to compare the result with theoretical calculation. Both analytical and theoretical power output produce is compared. This study proved that force and heat temperature does affect the power output and voltage output of the device. From the results, it shows that analytical calculation value is higher than theoretical calculation for voltage output and total power output for both air heat temperature and force by air flows parameter. The result shows the tendency of air heat temperature produce higher voltage output and total power output than force by air flow release.